Higher concentrations of serum iron and transferrin saturation but not serum ferritin are associated with cancer outcomes - Chua, A.; Knuiman, M.; Trinder, D.; Divitini, M.; Olynyk, John (American Society for Nutrition, 2016)
© 2016 American Society for Nutrition.Background: Although the carcinogenic potential of iron has been shown, evidence from observational studies that have linked serum iron variables and cancer outcomes has been inconsistent. Objective: We investigated whether higher iron concentrations increased risk of cancer outcomes. Design: A prospective examination of iron biomarkers as independent risk factors for cancer was assessed in 1597 men and 1795 women aged 25-79 y who participated in the 1994/1995 Busselton Health Survey and had relevant data, no history of cancer before the survey, and serum ferritin concentrations $20 mg/L. Follow-up for incident cancers and death from cancer was available to 2010. Proportional hazards regression modeling was performed to investigate if iron status predicted cancer incidence and mortality. Results: After adjustments for age, smoking, drinking, anthropometric and biochemical variables, or menopausal status (breast cancer), higher serum iron concentrations and transferrin saturation were associated with increased risks of incident nonskin cancer [HR for iron: 1.83 (95% CI: 1.21, 2.76; P , 0.01); HR for transferrin saturation: 1.68 (95% CI: 1.18, 2.38; P , 0.01)] including breast cancer [HR for iron: 2.45 (95% CI:1.12, 5.34; P , 0.05); HR for transferrin saturation: 1.90 (95% CI:1.02, 3.56; P , 0.05)] in women. Transferrin saturation was also associated with a greater risk of cancer death (HR: 2.48; 95% CI: 1.28, 4.82; P , 0.01). In men, higher iron concentrations were associated with reduced risks of incident nonskin cancer (HR: 0.65; 95% CI: 0.42, 0.99; P , 0.05) including colorectal cancer (HR: 0.34; 95% CI: 0.12, 0.95; P , 0.05). There was no association between serum iron and colorectal cancer risk in women. Serum ferritin was not associated with cancer risk or cancer death. Conclusions: Higher transferrin saturation or serum iron concentrations were associated with increased nonskin cancer risk and increased risk of cancer death. Conversely, in men, higher serum iron concentrations were associated with decreased risk of nonskin cancer. The molecular basis for the observed differences in the association between serum iron and nonskin cancer risk is unclear. Am J Clin Nutr 2016;104:736-42.